Optimalisasi Budidaya Perikanan Berkelanjutan Melalui Integrasi Recirculating Aquaculture System (RAS) dan Pengembangan Pakan Tepung Maggot di Desa Sumberharjo, Kecamatan Prambanan, Kabupaten Sleman - Tarigan, Abraham Renjaro; Pertiwi, Mahardika Bella Pertiwi; Ramadhana, M. Riski; Desy Putri Handayani (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
The vulnerability of aquaculture towards climate change and other environmental factors, forced the industry to adapt and adopt a new technology. Those factors can be minimized through the application of Recirculating Aquaculture System (RAS) that has been proven to have a 90–99% lower rate of water dependency compared to conventional aquaculture systems. Another problem faced by the aquaculture sector is the soaring production costs due to the high price of fish feed. Maggots are rich in protein, which is essential for fish growth, and can be used as a more affordable natural feed. Limited water supply in Desa Sumberharjo poses a significant obstacle to the development of aquaculture. This problem can be solved by utilizing RAS technology to overcome water limitations and developing maggot as an alternative feed to enhance productivity and reduce production costs in fish farming. The methods used in this research and community service are survey and field observation, program socialization, questionnaire, local group formation, alongside community training and assistance. This research and community service aims to address the challenges faced in developing the aquaculture sector in Desa Sumberharjo through the implementation of RAS technology and the development of natural fish feed from maggots.